Influence Of Human Resources On The Strategic Plan Development Among Smes In Machakos Town - Kimanthi, Ruth Wayua; Kilonzo, Thomas Muli; Nduta, Winnifred (Machakos University Press, 2021)
The purpose of this study was to establish the influence of human resource development on the strategic plan development among SMEs in Machakos Town in Kenya. Statement problem of this study evolved on the fact that SMEs have suffered in one way or the other from lack of or poorly developed strategic plans and are well aware of the negative impact. Past and previous studies were reviewed with the aim of identifying research gap and endeavored to fill the knowledge through this current study. This study was achieved by employing descriptive survey design on a sample of SMEs in Machakos for representativeness. Using questionnaire, document analysis and interview guide on selected participants from a population of the SMEs, research data was collected using questionnaires and interviews guides. Automatic inclusion and purposive sampling were employed sampling all respondents at the selected SME firms in Machakos Town. The data was analyzed descriptively with the use of analyzing techniques like inferential statistics among others of the SPSS and findings presented through tables and percentages. The conclusions evolved recommendations which included: training employees on strategic plan development and initiating motivation schemes to encourage employees to participate in strategic plan development.
Keywords: Human Resources Development; Strategic Plan Development; SMEs & Machakos Town